Characterization of Datuk Maringgih In the Script Siti Nurbaya: Wajah Di Sebalik Punggung Written by Edy Suisno - Ardafi, Yudhistino; Barkah, Hendri Jihadul; Susanti, Desi (Institut Seni Indonesia Padangpanjang, 2024)
Siti Nurbaya: Wajah di Sebalik Punggung, written by Edy Suisno, focuses on the character Datuk Maringgih. In the novel Siti Nurbaya by Marah Roesli, Datuk Maringgih is known as a cruel and greedy man. Datuk Maringgih is a rich old merchant who is considered evil because he married Siti Nurbaya as a debt to all of Siti Nurbaya's family debts. At first glance, Datuak Maringgih's actions look evil and detrimental to Siti Nurbaya. If you pay closer attention, taking into account the traditional aspects regarding the role of the Niniak Mamak in Minangkabau, as stated in the saying